The Influence of Experiential Marketing and Social Media Marketing on Repurchase Intention with Brand Trust as a Mediator for Lozy Hijab: Pengaruh Experiential Marketing dan Social Media Marketing terhadap Repurchase Intention dengan Brand Trust sebagai Mediasi pada Lozy Hijab - Rustiawati, Elis; Maesaroh, Syti Sarah; Prehanto, Adi (Indonesian Journal of Innovation Studies, 2025)
Background: The Muslim fashion industry in Indonesia has grown rapidly alongside the rising trend of modest wear and halal lifestyle. Specific background: Despite this growth, local brands such as Lozy Hijab face the challenge of sustaining customer loyalty in a competitive digital environment. Knowledge gap: Previous studies have not fully examined how experiential and social media marketing interact to shape brand trust and repurchase behavior within the modest fashion segment. Aims: This study analyzes the role of experiential marketing and social media marketing in shaping repurchase behavior, with brand trust as a mediating variable among Lozy Hijab consumers. Results: Using quantitative methods with 290 respondents analyzed through SEM-PLS, findings show that both experiential and social media marketing significantly build brand trust and repurchase behavior (R² = 0.599). Brand trust partially mediates these relationships, indicating that consumer experiences and digital interactions directly foster repurchase decisions. Novelty: This study highlights that in the Muslim fashion context, emotional experience and interactive communication can sustain consumer commitment even without full mediation by brand trust. Implications: The results guide local fashion brands to integrate experiential and digital strategies to strengthen consumer relationships and long-term competitiveness. Highlights Experiential and social media marketing jointly strengthen brand trust and consumer repurchase behavior. Consumer emotional experience and digital interaction drive repurchase decisions even without full brand trust mediation. Integrating online engagement and offline experience sustains customer loyalty in the modest fashion industry. KeywordsExperiential Marketing, Social Media Marketing, Brand Trust, Consumer Behavior, Repurchase Decision